Microglia induces Gas1 expression in human brain tumor-initiating cells to reduce tumorigenecity. Issue 1 (December 2018) - Sarkar, Susobhan; Poon, Candice; Mirzaei, Reza; Rawji, Khalil; Hader, Walter; Bose, Pinaki; Kelly, John; Dunn, Jeffrey; Yong, V.
Abstract We reported previously that microglia decreased the growth of human brain tumor-initiating cells (BTICs). Through microarray analyses of BTICs exposedin vitro to microglia, we found the induction of several genes ascribed to have roles in cell cycle arrest, reduced cell proliferation and differentiation. Herein, we tested the hypothesis that one of these genes, growth arrest specific 1 (Gas1), is a novel growth reduction factor that is induced in BTICs by microglia. We found that microglia increased the expression of Gas1 transcript and protein in glioblastoma patient-derived BTIC lines. Using neurosphere assay we show that RNAi-induced reduction of Gas1 expression in BTICs blunted the microglia-mediated BTIC growth reduction. The role of Gas1 in mediating BTIC growth arrest was further validated using orthotopic brain xenografts in mice. When microglia-induced Gas1-expressing BTIC cells (mGas1-BTICs) were implanted intra-cranially in mice, tumor growth was markedly decreased; this was mirrored in the remarkable increase in survival of mGas1-BT025 and mGas1-BT048 implanted mice, compared to mice implanted with non-microglia-exposed BTIC cells. In conclusion, this study has identified Gas1 as a novel factor and mechanism through which microglia arrest the growth of BTICs for anti-tumor property.